A Preliminary Look at Reasons for Attrition Among Special Educators Teaching Students with Autism Spectrum Disorder. (March 2023) - McFarland-Whisman, Jennifer; Whisman, Steven; Lockwood, Debra
Research on teacher retention and attrition suggests that it may be particularly difficult to fill special education positions in rural, economically disadvantaged, high-minority, and urban U.S. schools. Although teacher retention and attrition have received considerable attention in the literature, less is known about the reasons special educators teaching students with autism spectrum disorder (ASD) leave their positions. Using a series of surveys and follow-up phone interviews, the current study sought to provide preliminary information regarding reasons teachers of students with ASD in West Virginia, a predominantly rural, economically disadvantaged state, may leave their positions and identify the supports that may be most influential in assisting them in staying in their positions. Additional directions for research and ways school districts might better support teachers of students with ASD are discussed.